Novel 11β-HSD1 inhibitors: C-1 versus C-2 substitution and effect of the introduction of an oxygen atom in the adamantane scaffold. Issue 19 (1st October 2015) - Leiva, Rosana; Seira, Constantí; McBride, Andrew; Binnie, Margaret; Luque, F. Javier; Bidon-Chanal, Axel; Webster, Scott P.; Vázquez, Santiago
Graphical abstract